How much are US households prepared to pay to manage and protect whitebark pine (Pinus albicaulis Engelm.)? - Naughton, Helen T (Forestry (Lond), 2019)
The whitebark pine (Pinus albicaulis Engelm.) tree species faces precipitously declining populations in many locations. It is a keystone species found primarily in high-elevation forests across the Western US. The species is an early responder to climate change and qualifies for endangered species protection. We use contingent valuation to estimate the public’s willingness to pay for management of the whitebark pine species. In contrast, previous work centres on valuing broader aspects of forest ecosystems or threats to multiple tree species. While only approximately half of the survey respondents have seen whitebark pine, the mean willingness to pay for whitebark pine management is $135 per household. When aggregated across all households from the three sampled states, willingness to pay totals $163 million. This information is valuable to forest managers who must make difficult decisions in times of resource constraints and climate change.